The United Nations Security Council and Human Rights: Who Ends Up in the Spotlight?. Issue 4 (19th July 2022) - Allen, Susan Hannah; Bell, Sam R
Abstract: At the end of the Cold War, the United Nations Security Council broadened its view on what constitutes a "threat to international peace and security." With the rise of the concept of human security and increased focus on human rights, the Council has been more willing to act in response to domestic political issues such as human rights abuses. Despite an increased commitment to human security, the Council's attention on these issues has been uneven. What determines whose rights capture the Council's attention? What role do efforts by NGOs to "name and shame" play in the setting of the Council's agenda? We find that human rights abuses lead to countries being placed on the Council's agenda, but human rights organization naming and shaming results in more action by the Council—in terms of both meetings held and resolutions passed.